ROAD SAFETY AND TRAFFIC INJURIES DUE TO DISTRACTED DRIVING OF SMARTPHONE USAGE AMONG UNIVERSITY STUDENTS - Abd Rahman, R.; Sakim, N.; Lim, W. M.; Mohd Masirin, M. I.; Hassan, M. F. (Journal of Civil Engineering, Science and Technology, 2021)
This study provides the behaviour of university students using smartphone on daily basis and while driving, and exploring their perception towards the road safety of such habits. World Health Organisation states that distracted driving due to smartphone usage has been the uprising cause of road traffic injuries especially among young drivers. This study will provide knowledge in enforcing the right mitigation measures in preventing such behaviour from growing. The results from this study can also be integrated in intelligent transportation system in traffic accident prevention programme. This survey is conducted at Universiti Tun Hussein Onn Malaysia with a sample size of 371 respondents with majority of them aged 21 to 25 (86.6%) who own smartphone (100%) and private vehicle (59.1%). Results found that university student are dependent of their smartphone on daily basis for alarm (94.3%), communication and socialisation (73.9%). They tend to use their smartphone while driving, at traffic light (68.4%) and during traffic congestion (61.0%), often for maps navigations (69.8%) and to make call (57.4%) in hands-free mode. Despite knowing the danger of this behaviour (97.3%), they ignored the risks and committed such offenses. Hence, the need for education and enforcement are significant and relevant among university students to prevent such behaviours from growing.